Precision and accuracy of the new XPrecia Stride mobile coagulometer. Issue 156 (August 2017) - Piacenza, Francesco; Galeazzi, Roberta; Cardelli, Maurizio; Moroni, Fausto; Provinciali, Mauro; Pierpaoli, Elisa; Giovagnetti, Simona; Appolloni, Stefania; Marchegiani, Francesca
Abstract: Introduction: Oral anticoagulation therapy (OAT) with coumarins (vitamin K antagonist) is the most used against thromboembolism. Prothrombin time (PT) International Normalized Ratio (INR) monitoring is fundamental to establish coumarins dosage and prevent bleeding complications or thrombotic events. In this contest, the method and apparatus used for providing the INR measurements are crucial. Several studies have been published regarding the precision and accuracy of mobile coagulometers with different conclusions. No studies have been published regarding the new XPrecia Stride Mobile Coagulometer (Siemens). The aim of this work is to analyze precision and accuracy of the new XPrecia Stride mobile coagulometer to provide recommendations for clinical use and quality control. Materials and Methods: A total of 163 patients (mean age = 77.4 years old) under Warfarin OAT for whom the INR was assessed by both the traditional cs 2100i Sysmex and the new Xprecia Stride Mobile Coagulometer were included in this pilot study. Results and conclusions: The precision of the new mobile coagulometer resulted very good (CV < 3%). The analytical accuracy was also within the acceptable ranges of reliability (Lin's concordance = 0.962). Finally, the clinical accuracy was also acceptable (deviation > 15% from the true value in 20% of cases). Considering the overall results obtained by the new Xprecia Stride in comparison to that ones obtained from the other commercial devices, we can conclude that the new coagulometer is enough reliable for clinical settings. However, a larger trial to confirm these data is needed. Highlights: A reliable PT-INR determination is mandatory in order to identify the dosage of the oral anticoagulation therapy. INR results on both precision and accuracy of the new XPrecia Stride Mobile Coagulometer (Siemens) are presented. Precision showed very good results with a Coefficient of Variation < 3%. Analytical accuracy was found in line with the well known commercial devices. Clinical accuracy resulted acceptable (20% of cases with a deviation higher than 15%).